Entrepreneurship Verses Reinterpretation of Qur’an Surah Quraisy Based on Humanism Hassan Hanafi Theology - Karim, Abdul; Afandi, Yuyun (LPPM IAIN Kudus, 2020)
This qualitative research aims to comprehensively determine the gap between classical and contemporary interpretations of Qur’an Surah Quraisy that needs to be decomposed with the theological theory of humanism Hassan Hanafi, using the tahlili-muqaran interpretation method. The study found that the difference was apparent in explaining the term with the classical and modern interpretation methods used to define ilaf as habit or love and expertise in entrepreneurship, respectively. Furthermore, the word “Quraisy” is interpreted as a tribal name according to classical interpretation and branding in accordance with modern interpretations. The word rihlah is interpreted as a trade trip by classical interpretations, while in modern interpretation, it is known as an effort to maintain and improve quality. The word worship is interpreted as vertical and horizontal relationships by classical and modern interpretations, respectively. The differences are analyzed with the humanistic theology of Hassan Hanafi’s four points including, dialectics, eclectic, hermeneutics, and phenomenology. This research provides a new contribution to the interpretation of tahlili in collaboration with muqôron. It also tries to determine a common ground between classical and modern interpretations.